Coagulability in Obstructive Sleep Apnea - Christina Liak; Michael Fitzpatrick (Canadian Respiratory Journal)
BACKGROUND: Obstructive sleep apnea (OSA) is a common disorder that affects both quality of life and cardiovascular health. The causal link between OSA and cardiovascular morbidity/mortality remains elusive. One possible explanation is that repeated episodes of nocturnal hypoxia lead to a hypercoagulable state that predisposes patients to thrombotic events. There is evidence supporting a wide array of hematological changes that affect hemostasis (eg, increased hematocrit, blood viscosity, platelet activation, clotting factors and decreased fibrinolytic activity).